اعلان دولة لبنان الكبير 1919 - 1926 - العلكم، جهاد بادع كريم; الجابري، عباس حسين (الناصرية, 2015)
The importance of Big Lebanon as a subject arises as it is one of the salient events in the history of modern Lebanon .The new state of Lebanon has been a result of that event .It was mainly because of the French Policy that the big Lebanon came to being when the France and the Maron interment. France sent delegators to meet at the peace conference held in 1919. Aliyas AlHwaik presided over the mount of Lebanon delegation, which made its best to garn the French support in that important region. The researcher chose 1919 as his starting point due to the fact that the peace conference was held at that year in Parse .Then the idea of Big Lebanon was born as a result of Sykes-Picot between Britain and France. The researcher also did his best to answer some of the questions related to that period of time such as whether or not France was serious in establishing a Lebanese state and why. Another question is the role played by the sectarian coloring of Lebanon itself. The study is divided into four chapters preceded by an introduction and closed with a conclusion. Chapter One introduces the political situation of the Mountain of Lebanon till the end of WWI. This includes all the social, geo-political and other details in Mount Lebanon 1914-1918. Chapter Two concentrates on period from 1919-1920 when France and Lebanese delegations met in Pairs at the Pease conference .San Rimo conference is also discussed in this chapter which is divided into four sections. Chapter Three focuses on Lebanese local development between 1920 and 1926. Questions such as Lebanese census and the representative council of Lebanon and the standpoint of both Syrians and Lebanese forwards the new Lebanese state are all shed light upon in this chapter. Chapter Four discuses French trusteeship over Lebanon from 1920-1926. This Chapter is divides into four sections that have dealt with such issue as the French effect on Lebanese economic and political life, The France effect on the sacral life of Lebanon and its educational system. The conclusions sums up the findings of the study.
Keywords: لبنان -- الانتداب الفرنسي -- دولة لبنان الكبير -- الأحوال السياسية -- الحكم العثماني -- الدستور اللبناني، 1926م